A Descriptive Study to Assess the Knowledge Regarding Chandipura Virus and Its Prevention among 3rd Year B.Sc. Nursing Students at D.Y. Patil College of Nursing, Kolhapur - Ms.Vaishanvi Kharat; Ms.Tejaswini Misal; Ms.Tejal Gaonkar; Ms.Tanvimane; Mr. Viraj Patil; Mr.Yash Dakare; Mr.Yosi Gaikwad; Mr. Yash Chopade; Mrs. Richa Jadhav (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Chandipura virus (CHPV) is an emerging viral pathogen causing severe febrile illness and encephalitis, predominantly affecting children in India. This study aimed to assess the knowledge regarding Chandipura Virus and its prevention among 3rd year B.Sc. Nursing students at D.Y. Patil College of Nursing, Kolhapur. A descriptive design was used with a purposive sample of 86 students. Data were collected using a structured questionnaire. Results showed that 55% of participants had average knowledge, 26% had good knowledge, and 1% had poor knowledge regarding Chandipura virus and its prevention. Findings revealed a significant association between knowledge and demographic variables such as age, gender, religion, and area of residence. The study emphasizes the need for enhanced educational strategies, including workshops and curriculum updates to strengthen nursing students’ awareness of Chandipura virus. Objectives of the Study: 1. To assess the knowledge regarding Chandipura Virus and its prevention among Students of 3rd Year Bsc Nursing. 2. To find out an association between level of knowledge regarding Chandipura Virus and its prevention among Students of 3rd Year Bsc Nursing with their selected socio-demographic variables. Methods: A descriptive research design with a quantitative approach was used. Eighty-six third-year B.Sc. Nursing students were selected through purposive sampling. Data were collected using a structured questionnaire consisting of demographic details and 30 knowledge-based items on Chandipura Virus. Descriptive statistics such as mean, median, and standard deviation were used for data analysis, and the chi-square test determined associations between variables. Results: The findings revealed that 55% of students had average knowledge, 26% had good knowledge, and 1% had poor knowledge regarding Chandipura Virus and its prevention. The mean knowledge score was 18.96 ± 2.71. A significant association was found between knowledge levels and demographic variables such as age, gender, religion, and area of residence (p < 0.05). Interpretation: Although most students demonstrated moderate awareness, gaps persisted in understanding transmission and preventive strategies. This highlights the need for integrating updated content on emerging viral infections into nursing education. Conclusion: The study concluded that enhancing nursing students’ knowledge through structured educational interventions, seminars, and practical training is essential for improving preparedness against Chandipura Virus and similar vector-borne diseases.